Organic chemistry - Carey, Francis A (McGraw-Hill, 2003)
This text gives students a solid understanding of organic chemistry by stressing how fundamental reaction mechanisms function and how reactions occur. The book has over 300 new illustrations and seamless integration of reaction animations and molecular modeling exercises